LEGAL CONSEQUENCES OF THE JUDGE'S DECISION ON BIOLOGICAL CHILDREN FROM SIRI MARRIAGE - Ramadhani, Titania Isyani; Harahap, Burhanudin; Saptanti, Noor (JURNAL DARMA AGUNG, 2024)
Children born from a siri marriage can apply for the origin of children to obtain legal protection, as is the application for determination of the origin of children from siri marriage in the Karawang Religious Court Number: 440/Pdt.P/2023/PA.Krw. This raises the legal consequences between the biological father and the biological child determined by the Judge. The purpose of this study is to examine the legal consequences of the judge's determination of biological children from a siri marriage. The research used is normative legal research. The results of the study found that children from siri marriage who are determined as biological children should get the following rights: right to have an identity; right to sustenance and maintenance in the form of right to obtain education, health services, and obtain welfare; and inheritance rights through mandatory will. The obligation of the biological father to the biological child should be determined as sociologically obliged to protect the biological child so that the child is guaranteed and fulfilled the rights of the child so that the child can live, grow and participate optimally according to the dignity of humanity and get protection from violence and discrimination, the child becomes quality, good personality, and prosperous.